The ultrastructural localization of 60-kDa Ro protein and human cytoplasmic RNAs: Association with novel electron-dense bodies - Farris, A. Darise (The National Academy of Sciences of the USA, 1997)
The 60-kDa Ro ribonucleoprotein is an important target of humoral autoimmune responses. However, the ultrastructural locations of the 60-kDa Ro protein and its associated small cytoplasmic RNAs (Y RNAs) have not been previously determined, and the functions of the Ro protein and RNAs are not known. In this study, the cellular locations of the 60-kDa Ro protein and the Ro Y1 and Y4 RNAs are determined by immunoelectron microscopy and in situ hybridization electron microscopy, respectively. Both Ro protein and Y RNAs are concentrated in discrete areas of the nucleoplasm, nucleolus, and cytoplasm of cultured cells and human skin sections. The 60-kDa Ro protein and Y RNAs are also present diffusely in the cytoplasm, where they occur in ribosome-rich regions, and in the nucleus. The presence of Ro ribonucleoprotein components in nucleoli and in ribosome-rich cytoplasmic areas suggests a potential for the involvement of Y RNAs and/or 60-kDa Ro protein in ribosome synthesis, assembly, or transport. Double labeling experiments show that Ro protein and Y RNAs colocalize in the nucleoplasm, nucleolus, and cytoplasm. In addition, aggregates of Y RNA occur unassociated with 60-kDa Ro protein, and aggregates of 60-kDa Ro protein occur unassociated with Y RNA. Aggregates of both Ro protein and Y RNAs label previously unreported nuclear and cytoplasmic electron-dense bodies. We propose that these distinctive Ro-associated electron-dense bodies may represent structure(s) important for cellular transport and/or Ro function.